2016
DOI: 10.1002/ceat.201500282
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Filter Bag Failure and Method Development to Improve its Life Span

Abstract: Reasons for filter bag failure at steel plants were analyzed and a suitable approach to overcome such problems is proposed. Clean and used filter bags were tested to evaluate tensile and bursting strengths and air permeability properties. In order to simulate the behavior of the filter bags under acidic conditions normally encountered in actual working environment, an acid dew point test was conducted on the clean bags. The structural changes in all bags were determined by scanning electron microscopy. A signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Exposing uncoated PAN fabrics to H 2 SO 4 is found to decrease the tensile strength more than those coated with nanoclay. The nanoclay layer reduces the degradation of fibres by acting as a barrier between acid and fibres [15].…”
Section: Introductionmentioning
confidence: 99%
“…Exposing uncoated PAN fabrics to H 2 SO 4 is found to decrease the tensile strength more than those coated with nanoclay. The nanoclay layer reduces the degradation of fibres by acting as a barrier between acid and fibres [15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hybrid electrostatic precipitators with different filter bags have demonstrated significant advantages over conventional bag filters in terms of dust removal performance, cycle life, and energy consumption [7,8]. Some studies indicate that bag filters coated with a mixture of acrylic binder and nano-clay offer improved durability compared to normal bags [9]. Additionally, an operational parameter study found that the pressure drop across the fabric and the accumulated dust layer increased exponentially with increased dust loading on the filter [10].…”
Section: R = E^(-t/m)mentioning
confidence: 99%
“…Additionally, an operational parameter study found that the pressure drop across the fabric and the accumulated dust layer increased exponentially with increased dust loading on the filter [10]. Studies have also focused on factors such as filter pore size, fiber diameter, and filtration efficiency [11], optimization of filtration performance using multi-fiber filter bags [12], and the reasons for filter bag failures and methods to improve their lifespan [13].…”
Section: R = E^(-t/m)mentioning
confidence: 99%
“…This phenomenon makes the fabric around the seams loss the capacity of filtration. Thus, the seams result to the decrease usage rate of the filter bag [5,6]. The loss of the filtration efficiency was about 10%.…”
Section: Introductionmentioning
confidence: 99%